RATIONALIZATION OF BIPEDAL MOVEMENT - SPEED - Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Introduction. The primary aim of this investigation was to determine if the actual centers of bodily gravitation move in the same speed or whether their movements differ in speed, depending on the periods the speeds are observed, namely the period of resistance and the period of flight. Whereas the other aim of the investigation was to determine whether the sprint technique is typical only for the professional sprinters, or the same principles are valid to both medium and long-distance runners. Methodology. Analyzing kinograms we get special recording of the subject who is moving in front of the camera. The camera is fixed and its film records the positions of the subject while moving. This methodology allows us to record numerous positions in a time unit. During this research, camera made 60 records in each second. Contrary to the statistic research, kinematic methodology is not interested in a status of a population, but in a most rational way of movement, mainly with the regard to complex sport movements. As a principle, kinematic research uses the method of paradigm, i.e. it does not investigate the groups but the individual subjects. Moreover, it is a subject who has achieved the best result in the investigated domain. Results of the research. This research is primarily focused on the problem of the speed of the gravitational centre of the caudal part of the body, cranial part of the body, and the centre of gravity of the whole body. We aimed at determining the speed of the actual parts of the body at the athletic sprinters, medium and long-distance runners, who used maximum, medium, and low speed. After the measurements, we are given the following results: the speed of the gravitational centre of a sprinter's body in the phase of resistance, when he moved in a maximum speed, was 9.40 m/sec, the medium distance runner made 8.26 m/sec, while the long distance runner made 7.73 m/sec. Conclusion. Having in mind the biomechanical postulates of the running technique, we've come to a general conclusion that the differences in the running technique at variously specialized runners are, by a rule, of quantitative nature, i.e. as the speed decreases the step becomes shorter and the amplitudes of the swing become smaller. Typical of the rational running technique is the presence of the oscillatory movement of the longitudinal axis of the moving apparatus in the sagittal plane.